Nutrient stock and nutritional efficiency of woody species in dry tropical forest as reforestation indicators - Duarte Barbosa, Mozart; Freire, Fernando José; Marangon, Luiz Carlos; Patriota Feliciano, Ana Lícia; Barros de Andrade Lima, Rosival; Soares da Silva, Roseane Karla (Revista Ceres, 2025)
Efficient forest species can be indicated for reforesting environments, which present nutritional restriction. The objective of this study was to determine the nutrient stock in leaf biomass of the species of greatest importance value (IV) in a tropical dry forest fragment, as well as to evaluate the nutritional efficiency of these species as reforestation indicators. A phytosociological study of the woody species was carried out defining the ten species with the greatest IV. Three individuals of each species were selected and sampled, with 25 leaves being collected from the middle part of the crown of each individual. The N, P, K, Ca and Mg contents were determined in these leaves and the leaf biomass was estimated by an allometric equation, calculating the stock of these nutrients and the nutritional efficiency of the species. The Schinopsis brasiliensis and Mimosa tenuiflora species can be recommended in environments with restricted P availability, and Spondias tuberosa can additionally be indicated to populate areas with low levels of K and Mg in the soil. Differences in the nutritional efficiency of the species can be attributed to the differences in the absorption and translocation capacity, as well as the utilization of these nutrients.